Covid-19 Learning Concerning Financial Planning Importance and Household Accounting - Whedy Prasetyo (Jurnal Reviu Akuntansi dan Keuangan, 2020)
This study aims to identify the financial planning activities of individual households in dealing with Covid-19. Two regression models were used for the hypothesis test. Data were collected using a questionnaire with multi-staged methods, namely direct distribution and telephone. There are 59 individual household respondents in Malang Raya (Malang Regency, Malang City, and Batu City) - East Java, but 54 are complete and processed. The results showed that a significant relationship of individual behavior in household financial planning importance was strongly influenced by saving activities, focus on expenditures, emergency funds preparation, and attention to credit, so basic assumptions for expanding household financial planning based on individual household perceptions of responding to Covid-19 proved to be empirically consistent. Furthermore, household financial planning is the main factor in applying household accounting. This evidence has common goals for implementing a new mindset to responsibilities control of household financial transactions. A situation that is internal to the Covid-19 epidemic which requires social distancing of changes in the needs of a physical nature (economic shock)